Causes and prevention of revision surgery for preauricular sinus: A histopathological analysis. (January 2019) - Kim, Woo Jin; Lee, Yeo Myeong; Kim, Do Hun; Choe, Sihong; Lee, Donghoo; Park, Sung Yool; Kang, MiSeon; Cho, Hwa Jin; Heo, Kyung Wook
Abstract: Objective: Recurrence rates following preauricular sinus (PAS) surgery vary. Few studies have investigated recurrence after primary PAS surgery in histopathological terms. We performed a histopathological analysis of the causes of revision surgery for PAS, with a view to reducing the recurrence rate after primary surgery. Methods: We reviewed the medical records of patients who underwent revision surgery after primary excision of a PAS between 2002 and 2017. A pathologist reviewed the histopathology slides. Results: In total, 24 patients underwent revision surgery; of those, histopathology slides were available for 18 patients (19 revisions). The mean interval between primary and revision surgery was 50.4 months. We detected lumen with stratified squamous epithelium in 14 of the 19 (73.7%) revisions. Cartilage tissue was attached to the epithelial lining of the lumen in 14 of the 17 (82.4%) slides containing lumen. Inflammatory changes were found in all slides, and granulation tissue was detected in 10 of 19 revision surgery slides. Conclusions: To prevent PAS recurrence after primary surgery, we recommend a wide local excision including the inflammatory soft tissue, with concomitant partial removal of the cartilage of the ascending helix adjacent to the PAS.